THE IMPACT OF WORK DISCIPLINE AND MOTIVATION ON SERVICE PERFORMANCE: WORK ETHIC AS A MODERATOR IN THE AGRICULTURAL OFFICE OF TAMBRAUW REGENCY - Nelsan Mustamu; Wa Ode Likewati; Vebby Anwar (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
This study aims to analyze the influence of work discipline and work motivation on service performance, with work ethic as a moderating variable, among employees at the Department of Agriculture, Tambrauw Regency. A quantitative research methodology was employed to gather data from all 60 employees via questionnaires, interviews, and documentation. The results indicate that both work discipline and motivation have a significant positive effect on service performance, both partially and simultaneously. Moreover, work ethic is found to strengthen the relationship between work discipline and service performance but does not significantly moderate the relationship between work motivation and service performance. The findings highlight that work motivation is the dominant factor affecting service performance. These results suggest that improving service performance at the Department of Agriculture requires a balanced strategy that enhances both work motivation and discipline, supported by strong work ethics. The study recommends the implementation of motivational programs, enforcement of discipline policies, and cultivation of organizational values that foster integrity and responsibility among employees to achieve optimal service quality.